Magnetism in quantum materials probed by X-ray and neutron scattering - Rahn, M (2017)
In his programmatic article More Is Different (1972), Nobel laureate P. W. Anderson captured the fundamental interest in quantum matter in a nutshell. The central motive in this field is emergence. In the inaugural volume of the homonymous journal, J. Goldstein defined this as “the arising of novel and coherent structures, patterns and properties during the process of self-organization in complex systems". Famously, the idea that the "the whole is greater than the sum of its parts" goes back to Aristotle's metaphysics, and it has served as a stimulating concept in 19th century biology, economics and philosophy. The study of emergence in condensed matter physics is unique in that the underlying complex systems are sufficiently "simple" to be modelled from first principles. Notably, the emergent phenomena discovered in this field, such as high-temperature superconductivity, giant magnetoresistance, and strong permanent magnetism have had an enormous impact on technology, and thus, society. Historically, there has been a distinction between materials with localized, strongly interacting (or correlated) electrons — and non-interacting, itinerant electronic states. In the last decade, several new states of matter have been discovered, which emerge not from correlations, but from peculiar symmetries (or topology) of itinerant electronic states. The term quantum materials has therefore become popular to subsume these two strands of condensed matter physics: Electronic correlations and topology. In this thesis, I report investigations of four quantum materials which each illustrate present key interests in the field: The mechanism of high temperature superconductivity, the search for materials that combine both electronic correlations and non-trivial topology and novel emergent phenomena that arise from the synergy of electronic correlations and a strong coupling of spin- and orbital degrees of freedom. The common factor and potential key to understanding these materials is magnetism. My experimental work is focused on neutron and x-ray scattering techniques, which are able to determine both order and dynamics of magnetic states at the atomic scale. I illustrate the full scope of these methods with experimental studies at neutron and synchrotron radiation facilities. This includes both diffraction and spectroscopy, of either single- or polycrystalline samples. My in-depth analysis of each dataset is aided by structural, magnetic and charge transport experiments. Thus, I provide a quantitative characterization of magnetic fluctuations in an iron-based superconductor and in two Dirac materials, and determine the magnetic order in a Dirac semimetal candidate and a complex oxide. As a whole, these results demonstrate the elegant complementarity of modern scattering techniques. Although such methods have a venerable history, they are presently developing at a rapid pace. Several results of this thesis have only been enabled by very recent instrumental advances.